2024
DOI: 10.1039/d3ob01599h
|View full text |Cite
|
Sign up to set email alerts
|

Arylazo sulfones: multifaceted photochemical reagents and beyond

Ruchi Chawla,
Atul K. Singh,
Pradip K. Dutta

Abstract: The photochemical action of arylazo sulfones under visible light irradiation has recently gained considerable attention for the construction of carbon-carbon and carbon-heteroatom bonds in organic synthesis. The inherent dyedauxiliary group...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 150 publications
0
4
0
Order By: Relevance
“…Arylazo sulfones ( 27.1 , Scheme 27a) are crystalline, coloured (yellow to red) derivatives that bear a dyedauxiliary NN–SO 2 R moiety, capable of imparting both colour and photoreactivity to the starting compound (Scheme 1f). 35,36,141 Accordingly, upon visible-light irradiation, a N–S bond homolytic cleavage occurred from the 1 nπ* singlet excited state of 27.1 , producing a diazenyl radical 27.2 and the sulfonyl radical 27.3 . Aryl radical 27.4 is then released upon nitrogen loss from 27.2 , and such an intermediate has been applied in the development of a plethora of protocols for the formation of both C–C and C–heteroatom bonds.…”
Section: Reactions Via Carbon-based Radicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arylazo sulfones ( 27.1 , Scheme 27a) are crystalline, coloured (yellow to red) derivatives that bear a dyedauxiliary NN–SO 2 R moiety, capable of imparting both colour and photoreactivity to the starting compound (Scheme 1f). 35,36,141 Accordingly, upon visible-light irradiation, a N–S bond homolytic cleavage occurred from the 1 nπ* singlet excited state of 27.1 , producing a diazenyl radical 27.2 and the sulfonyl radical 27.3 . Aryl radical 27.4 is then released upon nitrogen loss from 27.2 , and such an intermediate has been applied in the development of a plethora of protocols for the formation of both C–C and C–heteroatom bonds.…”
Section: Reactions Via Carbon-based Radicalsmentioning
confidence: 99%
“…An exemplary case is that of arylazo sulfones J (Scheme 1f), obtained in two steps from anilines I and prone to generating several radical intermediates upon photolysis. 35,36 Saying so, the ideal case is the photochemical conversion of a (purposely designed) coloured compound into a valuable product without any additives, as it is the case for α-diazoesters K , which are widely used as precursors of carbenes L (Scheme 1g). 37…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Recent studies have found that arylazo sulfones usually work as effective aryl radical precursors to construct C(sp 2 )–heteroatom bonds. 69 In 2021, Yi et al developed an electroreductive radical thiolation/selenylation using arylazo sulfones as aryl radical donors, providing a transition-metal catalyst and reductant-free synthesis route to produce a series of decorated unsymmetrical thioethers and selenides (Scheme 33). 70 A hydrogenation product was isolated without a radical acceptor in 23% yield, which offered important evidence for the aryl radical mechanism.…”
Section: Diazonium Salts and Their Variations As Aryl Radical Precursorsmentioning
confidence: 99%